Scintigraphic diagnosis of infectious complications in renal failure patients undergoing hemodialysis, continuous ambulatory peritoneal dialysis or renal transplant - Vicente,Ana María García (2005)
Patients with end-stage renal disease have two therapeutic options, dialysis and renal transplantation. Infectious complications occurring in such patients will not only condition the effectiveness of such treatments, but are among the main causes of morbidity and mortality in such cases. Knowledge of the advantages and limitations of nuclear techniques is essential for management of these conditions.